Physicochemical degradation of phycocyanin and means to improve its stability: A short review - Aïda Adjali; Igor Clarot; Zilin Chen; Eric Marchioni; Ariane Boudier (Elsevier, 2022)
The cyanobacterium Arthrospira platensis, spirulina, is a source of pigments such as phycobiliprotein and phycocyanin. Phycocyanin is used in the food, cosmetics, and pharmaceutical industries because of its antioxidant, anti-inflammatory, and anticancer properties. The different steps involved in extraction and purification of this protein can alter the final properties. In this review, the stability of phycocyanin (pH, temperature, and light) is discussed, considering the physicochemical parameters of kinetic modeling. The optimal working pH range for phycocyanin is between 5.5 and 6.0 and it remains stable up to 45 °C; however, exposure to relatively high temperatures or acidic pH decreases its half-life and increases the degradation kinetic constant. Phycobiliproteins are sensitive to light; preservatives such as mono- and di-saccharides, citric acid, or sodium chloride appear to be effective stabilizing agents. Encapsulation within nano- or micro-structured materials such as nanofibers, microparticles, or nanoparticles, can also preserve or enhance its stability.